Analisis pengaruh kecepatan udara masuk PAWG terhadap volume kondensat, kinerja sistem, Psys dan COP - Ben V. Tarigan; Yohanes V. Gere; Muhamad Jafri; Defmit B.N. Riwu; Dominggus G. H. Adoe (Universitas Muhammadiyah Metro, 2023)
Water is one of the natural resources that is needed for the life of living things. Almost all activities require clean water, both for the metabolism of living things, agriculture and industry and is a major need. So that the availability of clean water sources needs to be maintained and looking for new sources. One source of clean water is atmospheric air which is very abundant. By using a water generator from stable atmospheric air, where the air enters the PAWG system in which there is a thermoelectric which can form a temperature difference in order to convert water into water vapor which then becomes condensate. The PAWG performance tested here is the inlet air velocity with variations of 0.27 m/s, 0.52 m/s and 0.97 m/s. The results show that the inlet air velocity affects the volume of condensate water and the performance of the Psys and COP systems. The higher the air velocity, the greater the volume of condensate water generated and the higher the Psys. But the results are different for COP, where the highest COP occurs at an inlet air speed of 0.52 m/s followed by a speed of 0.27 m/s and the smallest is 0.97 m/s.